ChemInform Abstract: Rapid Oxidation of 1, 2‐Diols, α‐Hydroxyketones and Some Alcohols Using N‐Bromosuccinimide in Ionic Liquid. Issue 41 (19th September 2013) - Khurana, Jitender M.; Chaudhary, Ankita; Kumar, Sanjay
Abstract A facile and clean synthetic protocol for the oxidation of the title alcohols to corresponding carbonyl compounds using NBS is developed.